Sosialisasi Etika Bisnis untuk Meningkatkan Kualitas Manajemen Usaha Pelaku UMKM di Desa Darussalam Kecamatan Bolo - Muhammad Yusuf; Eti Muliati; Gusmawarni Gusmawarni; Mihra Julianti; Odesa Ramadanti; Sakinah Sakinah (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Doing business, big or small, is bound up with ethical issues. Ethics refers to what a person should do morally. PKM activity partners are UKMs engaged in creative craft products made from acrylic/mute and knitted materials. located in Serang Banten. PKM activities aim to provide partners with knowledge about business ethics that partners need to have in doing business. Plus, partner businesses are located in densely populated areas. It is necessary to maintain ethical behavior where the partner's business is located. The method offered to partners/MSMEs is education/socialization using LEAFLET which is carried out door to door. . The material provided in the leaflet includes a discussion of (1) The role of ethics in business for UMKM, (2) Benefits of doing business for UMKM (3) Application of ethical principles in business in financial, marketing, production and HR activities. The results of the activity showed that partners were very enthusiastic in listening and discussing during the activity. Apart from that, it can provide knowledge about ethics in running a business.